Biochemical changes in Curimbatá subjected to transport stress and exposed to an agricultural fair - Durigon E.G.* (2019)
© 2019, Springer-Verlag London Ltd., part of Springer Nature.Fish known as Curimbatá (Prochilodus lineatus) suffered a reduction in natural stocks due to predatory fishing and environmental deterioration; these are among the reasons for increased interest in the inclusion of this species in agricultural fairs. The aim of this study was to evaluate whether transport and exposure to an agricultural fair alters plasma biochemical parameters in curimbatás. Blood samples were collected at 0 h (before transport), 10 h (end of transport), and 72 h (end of exposure to agricultural fair). Plasma cortisol levels increased after 72-h exposure to agricultural fair compared with initial collection (0 h). Plasma reactive oxygen species levels were lower in fish at 72-h exposure to agricultural fairs compared with those at initial collection, while plasma thiobarbituric acid reactive substances levels were higher after 10 h of transport than at initial collection (0 h). Plasma superoxide dismutase and glutathione S-transferase activities were lower after 10 h of transport than at initial collection, while plasma glutathione peroxidase activity was higher in fish exposed for 72 h at the agricultural fair compared with initial collection (0 h). Plasma total protein, albumin, and glucose levels were higher after 10 h of transport than at initial collection, while triglycerides levels were higher after 10 h of transport and 72-h exposure to the agricultural fair than at initial collection. The transport of these fish (average weight 209 g) for display agricultural fairs causes stress demonstrated by biochemical changes and increases in antioxidant enzyme activity, resulting in decreases of reactive oxygen species.